Design of a milling reactor coupled to a high-temperature mass spectrometer for thermodynamic/kinetic data of hydrogen-based materials. (19th January 2021) - El Kharbachi, A.; Nuta, I.; Artaud, L.; Collas, H.; Chatillon, C.
Abstract: Identification of species in the gaseous phase of hydride materials and their mixtures (e.g. LiBH4 –MgH2 ) is crucial for understanding the reactional mechanisms and diffusion kinetics of hydrogen across the different interfaces of phase segregation. This phase separation makes the characterization by conventional gas analysis techniques complicated and some analytical information could not be accessible. To overcome this surface/interface related issue, the study of the evolution of the gas phase emitted by the complex hydrides during ball-milling is considered. In this respect, an experimental set-up is designed by coupling a milling reactor with a mass spectrometer through a capillary tubing and an effusion Knudsen cell. A gas flow study (from molecular to viscous regimes) is performed in order to propose a suitable architecture of the entire device (ball-mill, capillary tubing, pipes, effusion cell compartment and pumping system) compatible with the mass spectrometric detection in terms of effused flow and molecular beam. Simulation of the flows and definition of their regimes nature at each stage of the pipes and vessels system is addressed as function of geometric parameters, upstream pressures, and pumping capacity on the downstream side (effusion cell). The study highlights the advantage of using a capillary tubing for the connection and ensure an optimal detection. Different working pressure conditions are demonstrated and associated to its length, meanwhile the diameter of the capillary has been demonstrated to be too sensitive to be varied. Graphical abstract: Image 1 Highlights: Hydrogenation processes depend on the solid-state interface/surfaces. Evolution of the gas phase during the course of milling is considered. A milling reactor is coupled to mass spectrometer through a capillary tubing. An optimized architecture is proposed based on flow calculation. This original device may allow advanced characterization of hydrogen materials.